2010
DOI: 10.1021/jo100087h
|View full text |Cite
|
Sign up to set email alerts
|

Reaction Discovery Using Microfluidic-Based Multidimensional Screening of Polycyclic Iminium Ethers

Abstract: Polycyclic iminium ethers are ambident electrophilic intermediates that react with a range of nucleophiles in a highly condition-dependent manner to afford densely functionalized lactams. In an effort to expand the scope of reactivity and assist in the generation of new chemotypes from these intermediates, several iminium ethers were subjected to reaction screening using an automated microfluidics reaction platform. Application of this approach led to the discovery of several interesting reaction pathways invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 38 publications
1
21
0
Order By: Relevance
“…The iminium ions 143 and 142 were readily obtained in 98% yield from the bicyclo[3.2.1]octanoid precursor 140 by an azido-Schmidt reaction. 91 Irradiation of an acetone solution of this mixture of regioisomers leads to the transformation of compound 142 (the only one which possesses the required b,g-unsaturated iminium pattern) via the aza-di-p-methane rearrangement, affording product 144 in 86% yield. This compound can undergo nucleophilic ring opening to afford cyclopropyl amides 145, 146, and 147 in high yields using previously described methodologies.…”
Section: Synthetic Application Of Odpm Photoisomerizationmentioning
confidence: 99%
“…The iminium ions 143 and 142 were readily obtained in 98% yield from the bicyclo[3.2.1]octanoid precursor 140 by an azido-Schmidt reaction. 91 Irradiation of an acetone solution of this mixture of regioisomers leads to the transformation of compound 142 (the only one which possesses the required b,g-unsaturated iminium pattern) via the aza-di-p-methane rearrangement, affording product 144 in 86% yield. This compound can undergo nucleophilic ring opening to afford cyclopropyl amides 145, 146, and 147 in high yields using previously described methodologies.…”
Section: Synthetic Application Of Odpm Photoisomerizationmentioning
confidence: 99%
“…We found that the oxa-di-π-methane rearrangement was limited to bicyclo[3.2.1]octanoids containing α,β-unsaturated ketones ( 6, 7, 10 ). For example, tertiary alcohol 12 2a and the ring-opened cycloheptenone 13 2a failed to react under direct irradiation or with triplet sensitization using benzoquinone.…”
Section: Resultsmentioning
confidence: 99%
“…2b Accordingly, photoirradiation of a mixture of 14 / 15 (Pyrex) in acetone afforded cyclopropane 16 (Scheme 3). Structure assignment was confirmed using 1D and 2D NMR analyses of hydrolysis product 17 .…”
Section: Resultsmentioning
confidence: 99%
“…The reaction represents an alternative to Schmidt reaction using hydroxyalkyl azides. [22][23][24][25][26][27][28] Studies of halogen-induced oxidative rearrangements of N,O-ketals were performed using 1a as a test substrate. Compound 1a was readily prepared by the condensation of cyclobutanone with a commercially available amino alcohol, 2-amino-3-phenylpropan-1-ol.…”
mentioning
confidence: 99%
“…The iminium ether intermediate ii has ambident electrophilicity, and the C2 and C4 positions of the oxazoline ring can react with nucleophiles. [22][23][24][25][26][27][28][30][31][32][33] Methyl ether 3a′ is not produced, and therefore nucleophilic attack by MeOH on intermediate ii selectively occurs at the C2 position rather than the C4 position of the oxazoline ring, to give a possible intermediate iii, which affords alcohol 3a on aqueous work-up.…”
mentioning
confidence: 99%